Produção de hidrogênio por via fotocatalítica empregando novos compósitos à base de SiO2 revestidos com TiO2 - Machado, Werick Alves (2020)
Developing a photocatalytic system and a highly efficient photocatalyst is still a challenge in the field of materials science. In this context, the present study aimed to synthesizing new core@shell photocatalysts, using SiO2 as a structural support and coating it with TiO2. The SiO2@TiO2 composites were synthesized in different proportions, with 25, 50, 75% w/w silica in relation to the TiO2 mass via modified sol-gel method, using acetone as a hydrolysis cosolvent for the titanium precursor. Then, the photocatalysts were characterized and the SiO2 coating was confirmed by scanning electron microscopy images together with the infrared spectra. The adsorption and desorption isotherms of N2 demonstrated that the composites are mesoporous materials with an average pore size between 3 to 4 nm with approximately 20% porosity. The surface area of coated oxides increased by 26% compared to uncoated oxide. Diffractograms and Raman spectra revealed crystalline materials with the coexistence of the anatase phases, as the main phase, and brookite as the secondary phase. In addition, diffractograms refined by the Rietveld method demonstrated that the composites maintained a proportion of approximately 75 and 25% of anatase and brookite phase, respectively. The band gap energy of the synthesized composites was slightly higher than the standard oxide (3.2 eV). After characterization, the photocatalytic potential of the composites was evaluated through the photocatalytic production of H2 under UV-vis irradiation on a bench scale. The most efficient composite (W50S50) produced 13.5 mmols of H2 in five hours of experiment, corresponding to a specific rate of H2 production of 32.5 mmol h-1 g-1. In the reuse assays, this same composite presented excellent stability in H2 production. However it was observed a reduction in its production of approximately 23% between the first and the last cycle, due to the consumption of sacrificial reagent. Then, this same composite was submitted to H2 production experiments in a solar simulator, producing about 25.0 μmols, equivalent of 48.0 μmols h-1 g-1, a value much higher than that reported in the literature in studies conducted under similar conditions. Finally, the efficiency of this composite in producing H2 using glycerol as a sacrifice reagent was evaluated using different concentrations of glycerol, achieving a production, under the best conditions, of only 1.75 μmols, corresponding to rate of 4.2 μmols h-1 g-1.